2018
DOI: 10.5943/mycosphere/9/6/4
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate-solubilizing characteristics of yeasts

Abstract: Phosphorus (P) is an essential element for plant development and metabolism. Because of its low availability and mobility in soils, it is often a limiting nutrient of plant growth. When phosphorus content in soil is insufficient, symptoms of phosphorus deficiency can appear, such as purple spots on leaves and stems or inhibition of development and maturation. To provide adequate nutrients for plant growth, appropriate fertilizers should be applied. However, overuse of chemical fertilizers can cause unanticipat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
5
2
Order By: Relevance
“…This suggests that the phosphate-solubilizing ability of yeasts is affected by exposure to soluble phosphate. In contrast, in a previous study, we found that some yeast strains still dissolve calcium phosphate in the presence of a high concentration of soluble phosphate (Kuo et al 2018 ). In 2017, Zeng et al reported that the growth and mineral phosphate solubilization of a phosphate-solubilizing bacteria (PSB), Burkholderia multivorans WS-FJ9, can be affected by exogenous soluble phosphate (Zeng et al 2017 ).…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…This suggests that the phosphate-solubilizing ability of yeasts is affected by exposure to soluble phosphate. In contrast, in a previous study, we found that some yeast strains still dissolve calcium phosphate in the presence of a high concentration of soluble phosphate (Kuo et al 2018 ). In 2017, Zeng et al reported that the growth and mineral phosphate solubilization of a phosphate-solubilizing bacteria (PSB), Burkholderia multivorans WS-FJ9, can be affected by exogenous soluble phosphate (Zeng et al 2017 ).…”
Section: Discussioncontrasting
confidence: 87%
“…pullulans JYC 104, in contrast, does not show solubilizing activity on either plate. In addition, in another earlier study, we found that the change in the pH of the medium is closely related to the phosphate-solubilizing ability of the yeasts (Kuo et al 2018 ). More soluble phosphate was dissolved in the medium with low pH.…”
Section: Resultsmentioning
confidence: 66%
“…This suggests that the phosphate-solubilizing ability of yeasts is affected by exposure to soluble phosphate. In contrast, in a previous study, we found that some yeast strains still dissolve calcium phosphate in the presence of a high concentration of soluble phosphate (Kuo et al 2018). In 2017, Zeng et al reported that the growth and mineral phosphate solubilization of a phosphate-solubilizing bacteria (PSB), Burkholderia multivorans WS-FJ9, can be affected by exogenous soluble phosphate (Zeng et al 2017).…”
Section: Discussioncontrasting
confidence: 78%
“…The phosphorus solubilization efficiency value was 3.34, higher than those recorded by Fu et al (2016), where the inoculum of S. cerevisiae was adjusted to an optical density of 0.10 at 600 nm. Conversely, the zinc solubilization efficiency (SE=2.58) was high but lower than those recorded in various strains of S. cerevisiae (10 8 cell mL −1 ) by Fernandez-San Millan et al, 2020. It is important to note that the solubilization of these compounds is associated with factors such as substrate concentration, medium pH, and temperature (Xiao et al, 2013;Nutaratat et al, 2014;Kuo et al, 2018). Therefore, it is advisable to take into account these potential discrepancies when comparing and analyzing reports on the solubilization of the compounds in question.…”
Section: Discussionmentioning
confidence: 95%